2009
DOI: 10.1111/j.1742-4658.2009.07087.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic disorder and coiled‐coil formation in prostate apoptosis response factor 4

Abstract: Prostate apoptosis response factor‐4 (Par‐4) is an ubiquitously expressed pro‐apoptotic and tumour suppressive protein that can both activate cell‐death mechanisms and inhibit pro‐survival factors. Par‐4 contains a highly conserved coiled‐coil region that serves as the primary recognition domain for a large number of binding partners. Par‐4 is also tightly regulated by the aforementioned binding partners and by post‐translational modifications. Biophysical data obtained in the present study indicate that Par‐4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 104 publications
2
37
0
Order By: Relevance
“…hPar-4 (59–77) is largely unstructured in aqueous solution, consistent with predictions and experimental data for the full-length protein 22 . This is evident from the 1 H – 15 N heteronuclear single quantum coherence (HSQC) spectrum that shows limited peak dispersion in the 1 H dimension (Fig.…”
Section: Resultssupporting
confidence: 84%
“…hPar-4 (59–77) is largely unstructured in aqueous solution, consistent with predictions and experimental data for the full-length protein 22 . This is evident from the 1 H – 15 N heteronuclear single quantum coherence (HSQC) spectrum that shows limited peak dispersion in the 1 H dimension (Fig.…”
Section: Resultssupporting
confidence: 84%
“…Although large-scale proteomics in cells have shown that caspases cut hundreds of proteins generally at a single site, only a few proteins, such as Bid, p28 Bap31, RIP-1, osteopontin and CYLD are reported as caspase-8 substrates [30-34]. The tumor suppressor protein PAR-4 predominantly comprises an intrinsically disordered protein, with ordered segments in the C-terminal domains of the protein [35]. In this study we demonstrate that caspase-8 cleaves PAR-4 after Asp 131, thereby separating the unstructured N-terminus from the C-terminal part, which includes the NLS-containing SAC domain and the leucine zipper.…”
Section: Discussionmentioning
confidence: 99%
“…48 NMR analysis revealed that an important regulator of proliferation and apoptosis, cAMPresponsive (CRE)-binding (CREB) protein (CBP), contains an intrinsically disordered ACTR-binding domain (residues 2059-2117) that completely folds upon binding. 49 Combined experimental and computational analysis revealed that N-and C-terminal regions of the human Nogo proteins 50 and C-terminal domain of a mitochondrial pro-apoptotic protein ARTS 51 are typical IDPRs, and that the prostate apoptosis response factor-4 (PAR-4), 52 prostate-associated gene 4 (PAGE4) protein, 53 and important oncoprotein c-Myc 54 are mostly disordered apoptosis-related proteins.…”
Section: Discussionmentioning
confidence: 99%